Correlations between autism spectrum disorders and childhood apraxia of speech. (13th April 2021) - Cabral, C.; Fernandes, F.
Abstract : Introduction: Autism Spectrum Disorder (ASD), is a neurodevelopmental disorder, characterized by inabilities in communication and social interaction. ¹ Childhood Apraxia of Speech (CAS) is a neurological disorder in which the consistency and precision of speech movements are impaired, in the absence of neuromuscular deficits. 2 Research indicates that children with ASD do not have a higher prevalence of CAS. 3 It is suggested that comorbid ASD and CAS would be expected to be extremely rare. Objectives: Verify the occurrence of CAS in children with ASD. Methods: The study included 22 children diagnosed with ASD aged between 4 and 8 years, who were undergoing speech therapy at a specialized health service and their therapists. The test was applied by the therapists Differential Assessment of Autism and Other Developmental Disorders (DAADD) 4, divides into six areas of development: language, pragmatic, sensory, motor, physical and behavioral to differentiate and diagnose disorders of neurological origin. Results: Among the 22 children participating in the research, 20 did not score the item apraxia. Only two children were referred with apraxia and twelve had receptive language and pre-academic skills proportional to their age. Of 22 participants, only three were overly excited for verbal productions. Conclusions: The analyzes of data suggests that the occurrence of CAS in children with ASD is low and underlying the disorder.